Association of gender and filled teeth based on DMFT index- A retrospective analysis of patient records - MANOHARAN, SUHAS; L. LEELAVATHI,; KUMAR. S, ARAVIND (The journal of contemporary issues in business and government, 2020)
Development of caries is multifactorial. Caries is a common disease of the tooth which when caught early can be treated by excavation and restoration of the tooth.Clinical and epidemiological studies show a consistent trend of caries prevalence with females having more caries occurrence than males.The aim of the study is to establish an association between gender and filled teeth.A retrospective study was done based on data analysed from 86000 patients records collected in a dental outpatient department.Excel tabulation was done and the results obtained from SPSS version 20. Statistical test performed was the chi square test.In the study a total of 4230 patients were included out of which 2328 were males and 1902 were females. Using the DMFT Index ,filled teeth status was acquired. Patients were grouped into three, based on filled teeth : 0- 7,8-15,15-21. On performing chi square test to find an association between gender and filled teeth, a P value of 0.887 was arrived at, which is not significant. Hence within limits of the study, it was found that there was no clinical and statistical association between gender and filled teeth based on DMFT index.